2017
DOI: 10.1038/gim.2016.109
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder views on secondary findings in whole-genome and whole-exome sequencing: a systematic review of quantitative and qualitative studies

Abstract: Purpose:As whole-exome sequencing (WES) and whole-genome sequencing (WGS) move into routine clinical practice, it is timely to review data that might inform the debate regarding secondary findings (SF) and the development of policies that maximize participant benefit.Methods:We systematically searched for qualitative and quantitative studies that explored stakeholder views on SF in WES/WGS. Framework analysis was undertaken to identify major themes.Results:Forty-four articles reporting the views of 11,566 stak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
136
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(144 citation statements)
references
References 68 publications
(397 reference statements)
6
136
1
1
Order By: Relevance
“…This may well be counterproductive, because many patients are very eager to receive at‐least actionable findings. This is consistent with other qualitative and quantitative studies that show that an overwhelming majority of patients would opt to know these results . Thus, an opt‐out is vital to ensure that patients feel respected but will hardly be used in practice.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This may well be counterproductive, because many patients are very eager to receive at‐least actionable findings. This is consistent with other qualitative and quantitative studies that show that an overwhelming majority of patients would opt to know these results . Thus, an opt‐out is vital to ensure that patients feel respected but will hardly be used in practice.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have shown that patients are generally positive about receiving unsolicited findings . This also holds true for cancer patients, but research suggests that patients become more cautious to receive all types of risk information when they are informed about the potential consequences for themselves and their family members . The possibility of encountering unsolicited findings makes clinical decision making in oncology even more complex, and a thoughtful disclosure policy is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Arguments for this cautiousness are the possibility of physical and/or emotional harm (by overwhelming patients with unnecessary or harmful tests, diagnoses or interventions) and hence the professional duty of non-maleficence [3,8]. When IFs are unintentionally identified, these results should only be disclosed if they are highly significant, highly penetrant and medically actionable [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Privacy and confidentiality have also been cited as reasons for declining participation in genome-wide association studies and repository-based research (Trinidad et al 2010). Participating in GS research presents distinctive considerations including the prospect of identifying unexpected or secondary findings (Mackley et al 2017), uncovering genetic variants in children that relate to adult onset conditions (Wilfond et al 2015), and disclosing carrier status findings in individuals not specifically seeking this information for reproductive reasons (Himes et al 2017). Though a lot is known about reasons for declining clinical genetic testing and genetic research, there is still much to explore regarding reasons patients decline GS.…”
Section: Introductionmentioning
confidence: 99%